Strategic management paper for Ayala Property Management Corporation - Mondragon, Hazel Joy L. (Animo Repository, 1998)
VISION Ayala Property Management Corporation envisions being the no. 1 property management corporation in the Philippines. We will set the industry standard that other will emulate and its name will be synonymous to property management. We will dominate the property management industry through our innovative, dynamic and dedicated people. THE COMPANY Ayala Property Management Corporation (APMC), a P363M company, is a wholly owned subsidiary of Ayala Land. Inc. (ALI) engaged in the business of providing integrated property management services, including building maintenance, lease administration, project management, commercial center management, subdivision maintenance, and technical consultancy services. Ayala Property Management Corporation belongs to the Business Management Services Industry. Companies under this category aim to satisfy the need of their clients for convenience and expertise in the management of their properties and assets. Within this industry, there are firms that have adopted very different competitive strategies: holding companies manage investments and other business undertakings project management companies manage real estate construction projects property management companies mange real estate. For purpose of identifying the opportunities and threats by APMC, we are limiting the scope of the industry analysis to the property management services industry. Professional property management is a relatively young industry in the Philippines. Up to the present time, most buildings have been controlled by administrators who rarely have professional management skills. However, as the cost of maintenance soars, owners are beginning to realize that they need professional managers to keep costs down and to maintain their properties to the consistently high international standards now being required.